2019
DOI: 10.3389/fnbeh.2019.00090
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Sleep Restriction in Developing Male Mice Results in Long Lasting Behavior Impairments

Abstract: Sleep abnormalities are prevalent in autism spectrum disorders (ASD). Moreover, the severity of ASD symptoms are correlated with the degree of disturbed sleep. We asked if disturbed sleep during brain development itself could lead to ASD-like symptoms, particularly behavioral manifestations. We reasoned that sleep is known to be important for normal brain development and plasticity, so disrupted sleep during development might result in changes that contribute to behavioral impairments associated with ASD. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In experimental studies on wild‐type (WT) mice, we have tried to address this question by chronically sleep restricting developing male and female mice [Sare, Levine, Hildreth, Picchioni, & Smith, 2015; Sare et al, 2019]. Even after a period of recovery sleep, we found that chronic sleep restriction resulted in long‐lasting social behavior deficits in male mice [Sare et al, 2015; Sare et al, 2019]. In female mice, we found increased social interactions following chronic sleep restriction [Sare et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies on wild‐type (WT) mice, we have tried to address this question by chronically sleep restricting developing male and female mice [Sare, Levine, Hildreth, Picchioni, & Smith, 2015; Sare et al, 2019]. Even after a period of recovery sleep, we found that chronic sleep restriction resulted in long‐lasting social behavior deficits in male mice [Sare et al, 2015; Sare et al, 2019]. In female mice, we found increased social interactions following chronic sleep restriction [Sare et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…2A and 2B), suggesting that distinct neural circuits underlie the shaping of these behavioral preferences and are vulnerable to sleep interventions at distinct developmental stages. More interestingly, both sleep manipulations, regardless in early childhood (Sare et al, 2016;Sare et al, 2019) or during adolescence (Fig. 3A and 3B), resulted to long-lasting behavioral changes in social interactions, highlighting the idea that sleep helps to shape the neural network underlying social behavior when it is still plastic during development, and the effects become "fixed" as the neural network matures in adulthood.…”
Section: Discussion: a Critical Period For Shaping The Neural Networkmentioning
confidence: 90%
“…A study using chronic sleep restriction during the early postnatal stage in mice (P5 -P42) showed that it induced a series of longlasting behavioral changes 4 weeks after the completion of sleep restriction, including hypoactvity in both sexes, slightly increased sociality and social novelty preference in female mice but not in male mice, and female-specific decrease of marble burying behavior (Sare et al, 2016). However, a most recent follow-up study from the same lab showed that the same postnatal sleep restriction in male mice indeed led to changes of social interaction behaviors, with sociality increased but social novelty preference impaired (Sare et al, 2019). The sleep restriction method used in these studies could be potentially problematic because its effects on sleep cannot be validated by EEG in mouse pups and the influence of maternal separation at this young age cannot be excluded, however results from these studies somewhat echoes with ours showing impairment only in social novelty preference but not in sociality preference by SD at later adolescence ( Fig.…”
Section: Discussion: a Critical Period For Shaping The Neural Networkmentioning
confidence: 99%
“…We chose to examine novelty-induced activity, anxiety-like behavior, and social behavior based on our prior experiments which showed that chronically disrupted sleep during development in WT mice had a long lasting effect on these behaviors ( Saré et al, 2015 , 2019 ). Interestingly, we noted that both caffeine and DORA-22 resulted in decreased activity in the open-field.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chronic sleep restriction beginning early in postnatal development in wild-type (WT) mice resulted in behavioral changes, particularly in social behavior and activity levels. The behavioral changes persisted even after recovery sleep ( Saré et al, 2015 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%